EVENT MANAGER IN THE CREATIVE INDUSTRIES: FUNCTIONS, COMPETENCIES, AND TRAINING PATHWAYS - Burnazova, Vira V.; Matiash, Serhii V. (Journal of Strategic Economic Research, 2025)
The article examines the profile of an event manager in the creative industries, which are currently one of the most dynamic and sought-after. The research problem lies in identifying the key functions, competencies, and training pathways for specialists capable of working effectively in the context of rapid changes in the event market and emerging technologies. The purpose of the study is to systematize and analyze the main components of the professional activity of an event manager, as well as to define effective models for personnel training in this area. The main hypothesis is that successful professional activity of an event manager is based on the integration of a creative approach, organizational skills, communicative competence, and digital awareness. The research methodology includes analysis of scientific literature, comparative analysis of professional standards, and generalization of educational program experiences. The results of the study allowed the authors to highlight a functional model of event manager activity, which includes creative-design, organizational-managerial, communicative, informational-digital, and reflexive-analytical components. In addition, current formats for specialist training were explored: higher education institutions, professional courses, and learning through practice. The conclusions emphasize the need for a comprehensive approach to professional training that combines theoretical knowledge and practical experience, as well as the continuous updating of competencies in the context of digital and social transformations.